Chemokine CXCL-1 Expression in the Subretinal Fluid during Rhegmatogenous Retinal Detachment. (December 2014) - Symeonidis, Chrysanthos; Androudi, Sofia; Rotsos, Tryfon; Moschos, Marilita M.; Souliou, Efimia; Dimitrakos, Stavros A.; Diza, Eudoxia
Abstract Purpose: To investigate the expression of chemokine CXCL-1 in the subretinal fluid (SRF) during rhegmatogenous retinal detachment (RRD) and identify potential correlations with number of quadrants involved and duration of the detachment. Methods and Results: Inclusion criteria were patients aged 18 years or older and primary RRD possibly complicated by proliferative vitreoretinopathy (PVR). CXCL-1 levels were measured in 36 SRF samples from 36 RRD patients. Mean CXCL-1 levels (102 ± 37 pg/mL) were significantly higher (p = 0.050) compared to controls. CXCL-1 levels correlated significantly with age (p = 0.001) and RRD duration (p = 0.002). Maximum CXCL-1 levels coincided with total RRD, 29- to 60-day duration and PVR grade C. Conclusions: The findings of this study may contribute to increased understanding regarding the role of CXCL-1 during the onset and progression of the wound healing process in the context of RRD and PVR.